2021
DOI: 10.1108/mbr-10-2020-0202
|View full text |Cite
|
Sign up to set email alerts
|

The role of market orientation and innovation capability in export performance of small- and medium-sized enterprises: a Latin American perspective

Abstract: Purpose This study aims to extend the existing base of knowledge of proactive and reactive market orientation and innovation capability by testing their impact on the export performance of emerging-market small- and medium-sized enterprises (SMEs) in a Latin American context. Design/methodology/approach This paper is a replication study, and its data were collected through a survey answered by general, marketing, sales or export managers at 155 Mexican SMEs. The research model was tested using partial least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 108 publications
1
22
0
1
Order By: Relevance
“…Previous researchers confirmed a relation among intensity, types of market orientation and degrees of innovation [ 40 , 49 , 50 , 54 , 61 , 78 ]. Both orientations are core requirements for competitive advantage and have proved a positive impact on innovation and BMI [ 30 , 78 , 80 , 86 , 89 ], Based on the above theoretical arguments, the researchers propose the following hypotheses:…”
Section: Introdutionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous researchers confirmed a relation among intensity, types of market orientation and degrees of innovation [ 40 , 49 , 50 , 54 , 61 , 78 ]. Both orientations are core requirements for competitive advantage and have proved a positive impact on innovation and BMI [ 30 , 78 , 80 , 86 , 89 ], Based on the above theoretical arguments, the researchers propose the following hypotheses:…”
Section: Introdutionmentioning
confidence: 79%
“…Reactive MO is market-driven which accepts market changes as given and displays more exploitative behavior through focusing on customers' existing needs and, accordingly, their reactions. As for proactive MO, it is market-driving which focuses on customers' latent and future needs through exhibiting more explorative behavior and developing new knowledge about the firm's markets, products, and capabilities [ 49 , 68 ]. Building on previous discussion, the researchers propose that:…”
Section: Introdutionmentioning
confidence: 99%
“…Likewise, previous studies have found relevant determinants of SMEs' EP in other export-drive countries, such as Thailand (Theingi, 2011), Vietnam (Safari and Saleh, 2020), Malaysia (Singh and Mahmood, 2014), Mexico (Acosta et al, 2018;Kolbe et al, 2021), Portugal (Sousa and Bradley, 2009;Prange and Pinho, 2017;Ribau et al, 2017;Rua et al, 2018) and Austria (Fuchs and Köstner, 2016). For instance, Theingi (2011) investigated the influence of SMEs' resources and export intermediary resources on EP using the RBV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Torkkeli and Fuerst (2018) studied the impact of the normative, regulative and cognitive structures on the IP of Colombian small and medium-sized enterprises (SMEs). Kolbe et al. (2021) explored how knowledge of proactive and reactive market orientation and innovation capability influence the Mexican SMEs’ IP.…”
Section: Introductionmentioning
confidence: 99%
“…Torkkeli and Fuerst (2018) studied the impact of the normative, regulative and cognitive structures on the IP of Colombian small and medium-sized enterprises (SMEs). Kolbe et al (2021) explored how knowledge of proactive and reactive market orientation and innovation capability influence the Mexican SMEs' IP. Furthermore, Losilla Solano et al (2019) point out that product diversification has a positive effect on firm's IP, and Bianchi et al (2017) presented that international entrepreneurial opportunity recognition and international networks mediate the relationship between international entrepreneurial orientation and Internet technology capabilities of SME performance.…”
Section: Introductionmentioning
confidence: 99%